The new class war: Excluding the working class in 21st‐century Britain. Issue 4 (March 2015) - Evans, Geoff; Tilley, James
<x xml:space="preserve">Abstract</x> Is Britain's working class already lost to a vicious cycle of political disengagement and exclusion? Geoff Evans and James Tilley outline the terms of a 'new class war' against the working class, based on its shrinking share of the population, low political participation rates and the decreasing return it provides to electoral vote‐chasers.